Peningkatan Kapasitas Guru-Guru SD di Kecamatan Tigaraksa dalam Pembuatan Video Animasi Menggunakan Canva Berbasis Artificial Intelligent - Wijayanti, Sri Hapsari; Marsudi, Almatius Setya; Oktorina, Megawati; Ratnasusita, Theresia Sri; Fransisca, Leoni (Universitas Medan Area, 2025)
Classroom learning at the elementary school level is reported to be more engaging when using animated videos. Canva is a widely used application for creating engaging and interactive educational videos. Canva's integration with artificial intelligence has simplified the process of creating educational videos. Teachers in Tigaraksa Subdistrict, Tangerang Regency, Banten, have been using Canva to create educational videos, but have never created them in animated format using Canva AI. The purpose of this activity is to improve the knowledge and skills of 38 elementary school teachers in Tigaraksa Subdistrict, Tangerang Regency. The activity began with a situation analysis, followed by preparation, implementation, assignment, monitoring, and evaluation. The activity was conducted on May 23 and June 13, 2025. The activity methods included simulation, training, and practice. The results of the activity showed that the increase in teachers' knowledge was moderate (0.50), and teachers' skills in making animated videos were considered good. It was evident that teachers were able to produce educational videos by utilizing the features available in Canva AI. Teachers demonstrated their digital skills by mastering AI-based Canva to vary teaching methods in the classroom.